Shopping experience in retail : How does the retailer improve the shopping experience of shoppers in terms of the different elements of retail concept? (2012)
Introduction. Actual context of the retail industry. Primary data information. Results of the interview. Analysis and conclusions of the interview. Recommendation for the retailers. Bibliography. Appendixes. List of graphics. List of tables. List of figures.